Effects of mulberry leaves treated with vitamin and esterol affect biological parameters of Bombyx mori L. - De Bortoli, Sergio Antonio; Takahashi, Roque; Miranda, José Ednilson; Dias, Luciane Sandrini; De Bortoli, Caroline Placidi; De Bortoli, Sergio Leandro Placidi (Comunicata Scientiae, 2012)
This study aimed to evaluate the effects of adding different concentrations of the leaf additivesnandrolone decanoate, ascorbic acid, retinol palmitate and retinol acetate on biologicalparameters of Bombyx mori larvae. The results showed that nandrolone and ascorbic acid, bothat 0.5%, provide the best value for the development of the larvae of B. mori, values which do notcorrespond to significant increases in cocoon and silk production; 1.0% of retinol palmitate shownegative effect to larvae development.